Дерида, семплот и слободната игра во дискурсот на ремикс културата - Ноневски, Вангел (Institute of Macedonian Literature, 2019)
To create something new from “the existing” is the paradigm of present-day remix culture. Several decades have passed since the global culture lost its faith in the search for “the new”, regardless if it was sought in the arts, the entertainment industry or music. We should not grieve the loss of that faith at all. The faith in the new is a faith in the sovereign author-god and in the concept of a complete and finished work of art. The sovereign author, who in pre-modern times was identified as the denominator of the undisputed semantic meaning of a work of art, is lost in the remixing process. Once a work/text becomes susceptible to reproduction, it is stripped bare of its author’s position as a sole determining factor of its semantic resonance. A DJ who mixes and manipulates a song replaces the author as an additional semantic attribute-factor, and the relationship is democratized and liberalized even further when we find out that the DJ mixes music according to the reactions of party-goers. In this equation, the audience actually becomes a chief procreative factor. This inherent interactivity of remix culture has intensified even more in the last 20-odd years with the emergence of new technologies and the internet, which enable every networked user (with a decent computer) to enter the potentially endless cycle of remixing any work of art/culture represented by new media.
Derrida, Sample and Free Play in the Discourse of Remix Culture
Keywords: Derrida, remix culture, hip hop, dub, sample, semantics, new media, modern art, Dada, deconstruction